Prevalence study of musculoskeletal disorders among bank workers - Gede Maheza Wiratama; Made Hendra Satria Nugraha; Ni Luh Nopi Andayani (Physical Therapy Journal of Indonesia, 2024)
Background: A formal worker is anyone who works for a business entity that has been registered at a government office. Those who work in the formal sector are identical to office work, with long duration of work, tend to be in a static position, and there are repetitive movements, thereby increasing the potential of musculoskeletal disorders (MSD). This can interfere with work productivity and work outcomes expected of formal sector workers. Methods: This study was a descriptive-analytic study with a cross-sectional approach with purposive sampling technique. Data was collected in June 2022 using a personal data questionnaire and the Nordic body map (NBM) questionnaire. Descriptive analysis was performed on the data using IBM SPSS 26 software. Results: Musculoskeletal complaints were found in the upper neck 8.8%, lower neck 6.8%, left shoulder 6.8%, right shoulder 5.4%, back 7.3% and waist 8.3%. Twelve people experienced moderate pain in the waist, 7 people experienced pain in the upper neck, and 2 people experienced very painful feeling in the waist. There were 35 respondents have a low MSD risk level 87.5% and 5 respondents have a moderate MSD risk level 12.5%. Conclusion: The respondents mostly had complaints around the upper neck, lower neck, left shoulder, right shoulder, back, and waist. There were risks of MSD in formal sector workers of risk of the MSD complaints experienced is predominantly low. The ergonomics approach can be applied to respondents with a higher level of risk. Keywords: Formal worker, musculoskeletal disorder, nordic body map, posture